2015
DOI: 10.1186/s13071-014-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cytauxzoon felis infection in healthy cats from enzootic areas in Arkansas, Missouri, and Oklahoma

Abstract: BackgroundInfection with Cytauxzoon felis in domestic cats can cause fever, lethargy, depression, inappetence, icterus, and often death. With a high mortality rate, cytauxzoonosis was historically considered a fatal disease. Within the last 15 years, cats with or without treatment have been recognized as chronically infected survivors of C. felis infection. Our objective was to determine the prevalence of C. felis in healthy domestic cats from Arkansas, Missouri, and Oklahoma.MethodsInfection with C. felis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…in the Iberian Peninsula is the more abundant wildcat [35]. Interestingly, recent studies have shown infection by C. felis in healthy domestic cats, supporting the idea that not only wild felids are competent reservoirs for this Cytauxzoon [42]. European domestic cats, especially those who roam freely, could be acting as reservoirs for the Cytauxzoon sp.…”
Section: Discussionmentioning
confidence: 99%
“…in the Iberian Peninsula is the more abundant wildcat [35]. Interestingly, recent studies have shown infection by C. felis in healthy domestic cats, supporting the idea that not only wild felids are competent reservoirs for this Cytauxzoon [42]. European domestic cats, especially those who roam freely, could be acting as reservoirs for the Cytauxzoon sp.…”
Section: Discussionmentioning
confidence: 99%
“…are protozoan hemoparasites belonging to the Piroplasmida Order that are transmitted by tick bites and infect a wide range of mammals worldwide (Meinkoth and Kocan, 2005;Penzhorn, 2006). C. felis has historically been viewed as highly fatal for domestic cats (Felis catus) while wild felids remain asymptomatic; however, recent studies have reported cats surviving infections as well as wild cats with fatal infections (Brown et al, 2010;Meinkoth et al, 2000;Nietfeld and Pollock, 2002;Rizzi et al, 2015). C. felis appears to be observed primarily in the southcentral regions of the United States of America (USA), where the disease has been extensively studied and the bob cat (Lynx rufus) has been identified as the natural reservoir of the parasite (Brown et al, 2010;Shock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a real-time PCR analysis of blood samples collected from clinically healthy domestic cats with a high risk of C. felis infections in Arkansas and Georgia showed that the prevalence rate of the parasite was 30.3% (27/89 cats) (33). More recently, a study of 902 domestic cats in Arkansas, Missouri, and Oklahoma by PCR yielded a 6.2% prevalence (37). A summary of data on nonfatal and clinically normal infections of the domestic cat and other felids is shown in Table 1.…”
Section: Nonfatal and Clinically Normal Infections In The Domestic Catmentioning
confidence: 99%
“…However, recent research has indicated that this scenario can also present the other way around. That is, some bobcats suffer from severe acute cytauxzoonosis, sometimes even leading to death, and in contrast, the domestic cat can be clinically normal or carry the parasite for a long period upon recovery from acute cytauxzoonosis (14,17,(33)(34)(35)(36)(37). It appears that the more we learn about the parasite and the disease, the more questions are being raised and need to be answered.…”
Section: Introductionmentioning
confidence: 99%